(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The term stress has been used to describe a wide range of situations and activities. Depending on whom you ask, stimulus may be anything from a simple thought to a complicated introspective state, while for others it’s a visible reaction to a stimulus or event, Environmental and internal pressures, as well as tensions among them, are referred to as adjustment. Adjustment is a phrase that’s often used to refer to things like mastery, defence, coping, or adaptability. Any reaction to external life stresses that helps prevent, minimize, or regulate external suffering might be considered a workable definition and the study which discussed about stress and adjustment among persons with movement disorders and the impact of different variable on stress, comparison of level of activities of daily living among persons with movement disorders with respect to different aspects of movement disorders.